Surveyor reference manual - Cole, George M. (Belmont, California : Professional Publications, 2015)
Resource added for the Civil Engineering Technology program 106071.
Mathematics Basics -- Field Data Acquisition -- Plane Survey Calculations -- Geodesy and Survey Astronomy -- Cadastral an Boundary Law -- Land Planning and Development -- Mapping -- Specialty Surveying Areas -- Computer Operations and Programming -- Business Management Practices -- Support Material.
Includes bibliographical references.
Keywords: SURVEYING HANDBOOKS, MANUALS, ETC